Pattern-oriented software architecture for dummies - Hanmer, Robert (--For dummies., 2013)
Implement programming best practices from the ground upImagine how much easier it would be to solve a programming problem, if you had access to the best practices from all the top experts in the field, and you could follow the best design patterns that have evolved through the years. Well, now you can. This unique book offers development solutions ranging from high-level architectural patterns, to design patterns that apply to specific problems encountered after the overall structure has been designed, to idioms in specific programming languages--all in one, accessible, guide. Not only will you improve your understanding of software design, you'll also improve the programs you create and successfully take your development ideas to the next level. Pulls together the best design patterns and best practices for software design into one accessible guide to help you improve your programming projects Helps you avoid re-creating the wheel and also meet the ever-increasing pace of rev cycles, as well as the ever-increasing number of new platforms and technologies for mobile, web, and enterprise computing Fills a gap in the entry-level POSA market, as well as a need for guidance in implementing best practices from the ground upSave time and avoid headaches with your software development projects with Pattern-Oriented Software Architecture For Dummies.